Permutation flowshop scheduling with simple linear deterioration. Issue 8 (3rd August 2019) - Sun, Lin-Hui; Ge, Chen-Chen; Zhang, Wei; Wang, Ji-Bo; Lu, Yuan-Yuan
ABSTRACT: This article addresses permutation flowshop scheduling problems with simple linear deterioration. The objectives are to minimize logarithm of the makespan, total logarithm of the completion time, total weighted logarithm of the completion time, and the sum of the quadratic job logarithms of the completion times. Approximation algorithms and their worst-case bounds are presented and analysed. Branch-and-bound algorithms are also proposed to solve the problems optimally. Computational experiments are performed to illustrate the algorithms.